Effects of explicit corrective feedback on writing skill: A private middle school example - Orhan Kocaman; Buse Nur Maral (Literacy Trek, 2022)
This study investigates and discusses the effects of explicit corrective feedback (ECF) on foreign language writing skills. In the process of learning a second language, the ability to write is one of the most important skills for gaining meaningful access to the target language. ECF is an indispensable part of practising writing while learning a second language. Despite the importance of ECF in language learning, many scholars often neglect the idea by accepting it as a behaviourist technique. The article first focuses on the definition of ECF and then reviews various research in the field. Besides, it discusses the research findings of the writing tasks applied to 43 private middle school students (B1 level) taking 5 subcategories into consideration. The study concludes that the research findings reveal a significant correlation between explicit corrective feedback and improving writing skills.